ANALISIS HAMBATAN PENJAMINAN MUTU SEKOLAH MENENGAH ATAS DI KABUPATEN TANA TORAJA - Tomas, Real (Satya Widya, 2025)
This study aims to describe the obstacles experienced in efforts to ensure school quality in Tana Toraja district. A qualitative approach with a multi-case study was used in this study to obtain information from facts in the field. Data were collected using in-depth interview techniques and documentation studies to support the data obtained. The collected data were analyzed using the Miles, Huberman, and Saldana interactive analysis model, which consists of three analysis processes, namely data condensation, data display, and conclusion drawing/verification. The validity of the data was tested using source triangulation and technique triangulation. The results of the study revealed that the obstacles experienced by schools included 4 aspects, namely the learning process, human resources, facilities and infrastructure, and costs. The learning process cannot be carried out effectively because schools lack the number of subject teachers, the low commitment of human resources in carrying out their duties and responsibilities causes educational activities not to achieve good quality, school facilities and infrastructure are not yet adequate for the needs of school residents, and educational financing cannot be managed properly by educational units.